Role of plant growth promoting rhizobacteria on Pteris vittata L as a potential hyperaccumulator plant for gold phytomining agent - Aminatun, Tien; Rakhmawati, Anna; Atun, Sri; Idrus, Arifudin; Sujangka, Arsyad (Brawijaya University, 2025)
Gold phytomining is the extraction of gold from the soil by harvesting specially selected hyperaccumulator plants. One of the potential plant species as a gold hyperaccumulator at the Ratatotok site, North Sulawesi, Indonesia, is Pteris vitata L, possibly because of the presence of rhizobacteria colonies in the roots to help the plant's resistance to metal stress in the soil. The isolation and identification show that the most resistant rhizobacteria to the gold stress is Pseudomonas aeruginosa RTKP1. The study aimed to assess the Pseudomonas aeruginosa RTKP1 to assist the gold bioaccumulation in Pteris vittata L. The phytomining test was carried out with four series of treatments for Pteris vittata L growing media, i.e., (1) tailings without compost and bacterial isolates, (2) tailings with bacterial isolates, (3) tailings with compost, and (4) tailings with compost and bacterial isolate. A descriptive analysis was carried out to analyze the role of the Pseudomnas aeruginosa RTKP1 on gold reduction in the media and gold bioaccumulation in Pteris vittata L. A quantitative analysis was carried out to analyze the bioaccumulation ability of Pteris vittata L with and without the addition of bacterial isolate. The role of the Pseudomonas aeruginosa RTKP1 is to increase the Translocation Factor (TF) and Biological Concentration Factor (BCF), particularly in the roots. The addition of compost to tailings as growing media for Pteris vittata L inhibits the effectiveness of the work of the Pseudomonas aeruginosa RTKP1 in increasing BCF and TF. However, this effect needs to be tested further to obtain significant results.